2018
DOI: 10.1097/01.naj.0000544948.27593.9b
|View full text |Cite
|
Sign up to set email alerts
|

CE: Too Much Sitting: A Newly Recognized Health Risk

Abstract: : While moderate-to-vigorous physical activity (MVPA) has been widely accepted as a major factor in promoting optimal health, emerging research specific to sedentary behavior suggests that MVPA alone may not be enough. This integrative literature review examines the evidence on sedentary behavior as an independent health risk for cardiometabolic health conditions, certain cancers, and all-cause mortality. In so doing, it reveals new insights into high-volume sitting and prolonged uninterrupted sitting and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 53 publications
1
22
0
3
Order By: Relevance
“…Our findings indicated that replacement of 30, 60, or 120 min of sitting time with standing promotes a reduction of 2.4%, 4.8%, and 9.7% for TC; 3.6%, 7.0%, and 14.3% for non-HDL-c; and 3.1%, 6.3%, and 16.2% for LDL-c. These findings are consistent with previous epidemiological and experimental studies [7,9,20,21,39,40,41], which show that reducing daily sitting time by approximately 60 min may probably be the minimum necessary to obtain clinical benefits, with further reductions resulting in greater health gain. Therefore, along with messages related to the accumulation of at least 60 min·day −1 of MVPA, adolescents should also be encouraged to sit less and stand more.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings indicated that replacement of 30, 60, or 120 min of sitting time with standing promotes a reduction of 2.4%, 4.8%, and 9.7% for TC; 3.6%, 7.0%, and 14.3% for non-HDL-c; and 3.1%, 6.3%, and 16.2% for LDL-c. These findings are consistent with previous epidemiological and experimental studies [7,9,20,21,39,40,41], which show that reducing daily sitting time by approximately 60 min may probably be the minimum necessary to obtain clinical benefits, with further reductions resulting in greater health gain. Therefore, along with messages related to the accumulation of at least 60 min·day −1 of MVPA, adolescents should also be encouraged to sit less and stand more.…”
Section: Discussionsupporting
confidence: 92%
“…In the TG analysis, it was observed that the replacement of sitting time with standing led to an increase in serum TG level. This result was somewhat unexpected, since the presumed hypothesis was that the enzymatic actions triggered by the muscular contractions necessary to assume the standing posture would cause a reduction of TG levels [9,38]. Therefore, it should be noted that the TG baseline was labeled as borderline, and this may have influenced this outcome.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations